Ultra-small wavelength splitters in a subwavelength plasmonic waveguide - Sun, Chengwei; Chen, Jianjun; Li, Hongyun; Qihuang Gong (Optics Letters, 2015)
Miniaturizing optical devices beyond the diffraction limit is of great importance for high-integration photonic circuits. By directly fabricating a double-slit aperture structure of different sizes in a subwavelength plasmonic waveguide, an ultra-small plasmonic wavelength splitter is realized experimentally. Due to the different slit widths, the surface plasmon polaritons (SPPs) in the opposite directions exhibit anti-phase interferences. As a result, the SPPs excited at different wavelengths can be split to propagate in the opposite directions along the subwavelength plasmonic waveguide. The plasmonic wavelength splitter only occupies a footprint of about 1.4 mu m(2) on the metal surface, and the splitting wavelengths and their separation can be easily varied by adjusting the structural parameters. This provides it with important applications in the areas of the optical modulating, sensing, and computing networks in highly integrated plasmonic circuits. (C) 2015 Optical Society of America